The effect on the surface activity and the structure of SPI caused by cleavage of disulfide bonds and by subsequent glucose modification. Issue 1 (January 2019) - Junfu, Fan; Junsheng, Li; Bixuan, Wang; Xin, Zhong; Guoxia, Huang; Liujuan, Yan; Xiane, Ren
The main purpose of this study was to investigate the effects on the molecular structure and the properties of soybean proteins isolate (SPI) after two modifications: (1) peracetic acid oxidative cleavage of its disulfide bonds and (2) the subsequent addition of covalently bonded glucose to the SPI containing the cleaved disulfide bonds. An appropriate amount of peracetic acid will be capable of enhancing the surface properties of SPI significantly; however, excessive oxidation can obtain undesirable results. When the concentration of peracetic acid was 0.4%, following by 35.5% of the disulfide bond cleavage, compared with those of natural SPI, the foaming capacity (FC), foaming stability (FS), emulsifying capacity (EC), and emulsifying stability (ES) of oxidized-SPI were increased by 82.0%, 65.8%, 58.5%, and 41.5%, respectively. The surface activity of oxidized-SPI could be promoted by glucose modification, and the FC, FS, EC, and ES of oxidized-SPI have further risen to 146.8%, 96.0%, 131.4%, and 40.3%, respectively, after the further glucose modification. Particle size measurements showed bimodality for the SPI that was modified with glucose with a portion of smaller sizes seen. Fluorescence spectroscopy and circular dichroism measurements demonstrate that extensibility increases; flexibility is enhanced; and glycosylation occurs more readily due to the oxidation of SPI. When grafted with glucose, these oxidized soybean protein products produce more ideal foaming and display better emulsification properties.